The Effects of ASEAN Economic Community (AEC) Blueprint Adoption on Intra-ASEAN Trade on Manufacturing Products - Liew, Venus Khim-Sen; Wong, Colin Koh King; Mohammad Affendy, Bin Arip (Human Resource Management Academic Research Society, 2020)
This paper seeks to explore the effects of ASEAN Economic Community (AEC) Blueprint adoption since 20 November 2007 on the bilateral manufacturing trade between the ASEAN member countries and their trading partners. Ten ASEAN member countries and their 39 trading partners are considered in this study. A panel with model with AEC dummy variables is estimated on a set of panel data over the sample period of 1995 to 2014.